MODEL BUKU TEKS PELAJARAN BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI - Oos M. Anwas (Balai Besar Guru Penggerak Jawa Timur, 2016)
Innovation on book industry, textbooks of particular, tends to be relatively static, eventhough the demand and the development of ICT advances very fast. This article aims to study the benefits and the development model of ICT based textbooks. This article applies a review method of relevant literature. The results show that the benefits of ICT-based textbooks are among others: enabling the content presented in multimedia format so that it becomes more attractive and easily understood, learning becomes more active, variety, interactive, more productive in efficient manner, and in line with the development trend of the digital native generation.The ICT-based textbooks development can be packaged in audiobooks and e-books. The development of audiobooks and e-books is done by repackaging the printed books into audio media by optimizing dialogue or monologue, music, and sound effects aspects.The development model of e-books and audiobooks is done by changing the printed book content into digital format including the text, images, audio, video, animation, and interactive simulations according to the characteristics of the lesson content. The study concluded that ICT-based textbooks needs to be developed in the models of audiobook and e-book by presenting the learning content in multimedia format so that it becomes more attractive and easily understood by learners. AbstrakInovasi industri perbukuan terutama buku teks pelajaran cenderung statis, padahal tuntutan dan perkembangan Teknologi Informasi dan Komunikasi (TIK) sangat pesat. Tulisan ini bertujuan untuk mengkaji manfaat dan model pengembangan buku teks pelajaran berbasis TIK. Tulisan ini menggunakan metode kajian literatur yang relevan. Hasil kajian menunjukkan bahwa manfaat buku teks pelajaran berbasis TIK antara lain: menyajikan konten mutimedia sehingga lebih menarik dan mudah dipahami; belajar lebih aktif, variatif, dan interaktif; secara produksi lebih efisien; serta sesuai dengan trend perkembangan generasi digital native. Pengembangan buku teks pelajaran berbasis TIK dapat dilakukan melalui model audiobook dan e-book. Pengembangan model audiobook dilakukan dengan cara mengemas buku cetak ke dalam media audio dengan mengotimalkan aspek: dialog/monolog, musik, dan efek suara. Pengembangan model e-book dilakukan dengan cara mengubah sajian konten buku cetak ke dalam format digital, meliputi unsur: teks, gambar, audio, video, animasi, dan simulasi interaktif sesuai dengan karakteristik dari konten pelajaran tersebut. Kajian ini menyimpulkan bahwa buku teks pelajaran berbasis TIK perlu dikembangkan baik model audiobook maupun e-book dengan menyajikan konten pembelajaran secara multimedia sehingga lebih menarik dan mudah dipahami oleh peserta didik.